Efeitos de áreas urbanas sobre a estrutura ecomorfológica das assembleias de peixes de riachos. - Pessoa, Leonardo Antunes (2018)
The objective of this paper was to analyze the effects of urban areas on the ecomorphological structure of stream fish at the scale of mesohabitat. The hypothesis tested was that those mesohabitats inserted in urban streams would present lower species diversity and, consequently, smaller ecomorphological space volume, but interspecific morphological similarity would remain constant (i.e. decrease in ecomorphological diversity). For this purpose, environmental and fish fauna data were collected on the mesohabitats (riffle, run and pool) of five urban streams and five rural streams. After, 22 ecomorphological proportions were obtained through the means of linear morphological measurements related to the trunk, fins, head and mouth of the fish. Principal Component Analysis were developed to: (i) order collection points according to their environmental characteristics and (ii) characterize the trend of interspecific variation in the multivariate ecomorphological space between fish assemblages. The taxonomic structure was determined by comparing the Shannon Diversity Index between the mesohabitats of urban and rural streams. On the other hand, the ecomorphological structure was determined by calculating the Euclidean Distance between the scores of each pair of species in the first four PCA axes, in order to obtain ecomorphological distances (i.e., DMC, DMVMP and DPDMVMP). Rural mesohabitats differed from the urban ones by the structure of its environmental components, as well as by the ecomorphological distances, nevertheless, there was not significant difference in species diversity. Thus, the larger Euclidean Distances in the urban mesohabitats showed that these environments are more dissimilar morphologically than the rural mesohabitats. Therefore, the results show that, opposing the initial hypothesis, the reduction of fish diversity at mesohabitat scale was related to the smaller interspecific morphological similarity and to the greater volume of the ecomorphological space.